Government Responsibilities in the Health Services of the Indonesian People Post the Implementation of the New Health Law - ., Ardiansah; Asnawi , Eddy; Pardede , Rudi (Journal of Ecohumanism, 2025)
Purpose: This research investigates the rationale for employing the Omnibus Law method in the enactment of Indonesia’s New Health Law, scrutinizes the liberalization of health services within it, and assesses the government’s obligations post-implementation. Theoretical Reference: Utilizing normative legal research and an analytical framework, this study examines the legal provisions and implications of the New Health Law, particularly regarding government responsibilities and health service liberalization. Method: This research employs normative legal analysis and an analytical approach to assess the legal, social, and constitutional dimensions surrounding the New Health Law and its impact on Indonesian health services. Result and Conclusion: The study finds that while the government aims to address health sector challenges and strengthen regulations through Law Number 17 of 2023, concerns arise regarding the removal of mandatory health sector spending. This raises constitutional and ideological questions, highlighting the need for judicial review to uphold government responsibilities in providing comprehensive health services. Implications of Research: This research underscores the importance of aligning health policies with Indonesia’s foundational principles, ensuring legislative measures prioritize citizen welfare and uphold constitutional mandates. Originality/Value: Contributing to existing literature, this research offers insights into the legal and policy implications of Indonesia’s New Health Law, informing future debates and potential reforms in the healthcare sector.